Genetics of adolescent idiopathic scoliosis. - Czeizel, A (1978)
A genetic family study was undertaken by photofluorography of the first, second, and third degree relatives of 116 index patients with adolescent idiopathic scoliosis (AIS). The index patients were ascertained in the course of an epidemiological screening. The pattern of familial clusters and the recurrence risk related to the number of affected relatives and to the severity of the disorder in the index patients support the theory of polygenic inheritance, a multifactorial-threshold aetiological model. The recurrence risk table for first degree relative, prepared by computerised data processing and analysis, may contribute to the early diagnosis and prevention of the disorder.